FAKTOR RESIKO KEKAMBUHAN HIPERTENSI PADA LANSIA DI WILAYAH KERJA PUSKESMAS SINTUK KABUPATEN PADANG PARIAMAN TAHUN 2020 - Syntia Veronica Rozana (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
Hypertension or high blood pressure is also known as the silent killer. WHO reports that hypertension is estimated to cause 7.5 million deaths. The purpose of this study was to determine the risk factors for recurrence of hypertension in the elderly in the work area of the Sintuk Public Health Center, Padang Pariaman Regency. This type of research is observational study with a case-control design approach, the subjects of this study were the elderly aged 60 years. The population in this study were all elderly people seeking treatment at the Sintuk Health Center. The sampling technique used is purposive sampling. Data collection was obtained by using a questionnaire. The analysis of data using Chi-square test. The results showed that there was a relationship between family support (p = 0.005), sleep quality (p = 0.005), salt consumption (p = 0.005), coffee drinking habits (p = 0.002), stress level (p = 0.000), drinking compliance. drugs (p=0.011), and complications of other diseases (p=0.000) with recurrence of hypertension in the elderly. There was no relationship between age (p=0, 598), physical activity (p=0,785).